2019
DOI: 10.1074/jbc.ra118.005094
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA in CB1 antagonist–mediated regulation of adipose tissue macrophage polarization and chemotaxis during diet-induced obesity

Abstract: Although cannabinoid receptor 1 (CB1) antagonists have been shown to attenuate diet-induced obesity (DIO) and associated inflammation, the precise molecular mechanisms involved are not clear. In the current study, we investigated the role of microRNA (miR) in the regulation of adipose tissue macrophage (ATM) phenotype following treatment of DIO mice with the CB1 antagonist SR141716A. DIO mice were fed high-fat diet (HFD) for 12 weeks and then treated daily with SR141716A (10 mg/kg) for 4 weeks while continuing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…We adopt miR-128 inhibition to significantly improve the occurrence of diabetic bladder disease in rats and we have found for the first time that miR-128 can target the inhibition of CB1 expression. Previous studies have shown that CB1 can cause Inflammation, inflammation plays an important role in the development of diabetes [27]. Our high expression of CB1 can antagonize the promotion of miR-128 on the occurrence of diabetic bladder disease.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…We adopt miR-128 inhibition to significantly improve the occurrence of diabetic bladder disease in rats and we have found for the first time that miR-128 can target the inhibition of CB1 expression. Previous studies have shown that CB1 can cause Inflammation, inflammation plays an important role in the development of diabetes [27]. Our high expression of CB1 can antagonize the promotion of miR-128 on the occurrence of diabetic bladder disease.…”
Section: Discussionmentioning
confidence: 52%
“…miR-128 inhibits growth and mediates differentiation by targeting oncogenic receptor tyrosine kinase (RTK) epithelial growth factor receptor and platelet-derived growth factor receptor alpha. [12] miR-128 is a glioma tumor suppressor that targets RTK signaling to inhibit giNSC self-renewal and enhance differentiation [27]. These results suggest that miR-128 plays a key role in DCP.…”
Section: Discussionmentioning
confidence: 89%
“…It has been indicated that IL-25 stimulates alternatively activated macrophages and their interaction with adipocytes but promotes energy metabolism, enhances mitochondrial functions and attenuates lipid accumulation in the liver and adipose tissues [ 22 ]. In addition, cannabinoid receptor 1 (CB1) blockade resulted in downregulation of miR-466 family and miR-762 in ATMs, which promote M2 polarization and macrophage egress from adipose tissue [ 23 ]. Empagliflozin, a sodium-glucose cotransporter (SGLT) 2 inhibitor, repressed weight gain by enhancing browning of adipocytes and alleviated obesity-induced inflammation and insulin resistance by polarizing M2 macrophages in WAT and the liver [ 24 ].…”
Section: Macrophage Polarization In Adipose Tissuesmentioning
confidence: 99%
“…Reductions in weight and fat mass after four weeks were again significant in rimonabant-treated DIO mice fed a high-fat diet, yet lean tissue mass was retained and not significantly different to the vehicle treated-mice (20.08 ± 0.29 g vs. 22.9 ± 0.11 g). Furthermore, rimonabant proved to decrease inflammation by downregulating several microRNAs in adipose tissue macrophages, inducing an anti-inflammatory cascade [ 48 ].…”
Section: Exploring the Direct Effects Of Cannabinoid Drugs On Bodymentioning
confidence: 99%